Changes in the sex ratio of the Common Pochard Aythya ferina in Europe and North Africa - Brides, Kane; Wood, Kevin A.; Hearn, Richard D.; Fijen, Thijs P.M. (Wildfowl, 2017)
Assessments of the sex ratio among Common Pochard Aythya ferina flocks were undertaken in countries across Europe and into North Africa in January 2016, for comparison with results from surveys carried out over the same area in January 1989 and January 1990. The mean (± 95% CI) proportions of males in the population were estimated as 0.617 (0.614–0.620) in 1989–1990 and 0.707 (0.705–0.710) in 2016; this difference between surveys was found to be highly significant. Whilst male bias increased with latitude in both surveys, this relationship was weaker in 2016 as the increases in male bias between 1989–1990 and 2016 were greater in countries further south. Given that the sex ratio of Pochard broods is approximately 1:1 at hatching, the strong male bias observed among adult birds is indicative of lower survival of females compared with males. The results of this study suggest that factors adversely affecting female survival rate (relative to that of males) may partly explain the decline in overall Common Pochard abundance. Given the widespread and ongoing decline of this species throughout most of Europe and North Africa, further information on possible demographic drivers of change is urgently required.